Effect of volume cavity at various distances for thermal cooling pumping jet device / Aizat Fadzli Ayob - Ayob, Aizat Fadzli (2017)
Space is a major constraint in electronic cooling to dissipate heat that can cause overheating to the device. Synthetic jet is an air based cooling system that developed without the use of fans to its flow. Due to the intake and eject for high velocity working fluid from a single opening makes synthetic jets are zero-net-mass-flux.This research was focused on the effect of volume cavity at various distance between the nozzle to heated surface and effect of volume cavity at various frequency. Three experiments have been conducted during the study which were experiment of heater characteristic, external and internal temperature and fluid air velocity for the fabricated synthetic jet.. The experiment using heater of 24 V; 100 W. The power input were used to determine the consistent heater surface temperature at 343.15 K.Five different volume have been used in this research. Each volume were tested from 300 Hz to700 Hz driving frequency at 50 mm distance nozzle to heated surface. Result show that, high temperature reduction for model 1 at 500 Hz (431.75 K) compare to other driving frequency. It given that 500 Hz is the resonance frequency that has maximum amplitude. Maximum temperature reduction was obtained at 50 mm distance. Maximum air velocity for all model of synthetic jet were located at distance of 10 mm while minimum air velocity located at 70 mm Model 1 of synthetic jet were given the highest air velocity and lowest air velocity which is 1.29 m/s and 0.08 m/s respectively